Pilkada 2020: Jeda Politik Kekerabatan di Kabupaten Minahasa Selatan - Katerina Bataha; Kharisma Bataha (Bestuurskunde: Journal of Governmental Studies, 2021)
Kinship politics may be a way to preserve the power of the elites through elections.  With the strong support of kinship politics from the local political elite, the candidate for the South Minahasa district head, Michaela Paruntu, had a very high chance of winning the 2020 regional election in the South Minahasa District. But the reality was different. The popularity gained from the influence of the previous district head, a close relative of the candidate, and the support of the ruling party in the South Minahasa District were ineffective in generating public support for the candidate. This study analyzed the factors that caused the ineffectiveness of the kinship politics in the South Minahasa District. This phenomenon was interesting to study since previous studies on kinship politics presented empirical evidence that candidates who have a kinship with the authorities or elites have a better opportunity to win an election. This study used a qualitative method with a case study approach. The result of the study showed that the community's perception of kinship politics in the South Minahasa District influenced people's political choices in the 2020 Regional Head Election (Pilkada).